Direção espiritual: contribuições teológico-filosóficas ao aperfeiçoamento da vivência Cristã - Manso, Márcio Rogério (2019)
The spiritual guidance presupposes the search and a diligence both achieved through a continuous process of interior liberation, of discernment of the advisee and of decisions almost always arduous and put into practice from many obstacles. This occurs for two reasons: the first one is that man is a human being in constant maturation and growth. The second is that he presents fragility as part of his nature. His work must consist in finding, on a progressive path, the concrete attitudes and gestures from which his existential purpose must be constituted. The guidance of the spiritual advisor, shared with the advisee, will comprise of an exhausting quest. However, the advisee will be responsible for the inward-looking to free himself, for presenting himself in total openness to the Father, for examining the stimulus of his Spirit and distinguishing what he desires, through practical consequences. In order to avoid the dangers of arbitrariness, illusions and deceptions, we will use, in the pastoral practice, Luigi Maria Rulla's Self-transcendence in Consistency theory for the opening of the advisee's field of freedom aiming at his humanization and therefore, the increase in the Christian life